ANALISI KOMPARATIF KINERJA KEUANGAN ANTARA PT. INDOMARCO PRISMATAMA ( INDOMARET ) DENGAN PT. SIGMANTARA ALFINDO ( ALFAMART ) - -, Diana Wati (EKONOMIA, 2019)
The purpose of this study is to find out and analyze financial performance from aspects of liquidity, profitability aspects, and solvability aspects in 2013 up to 2015 on the financial performance of PT. Indomarco Prismatama (Indomaret) with PT. Sigmanatara Alfindo (Alfamart).The analytical method used in this study is the liquidity aspect including current ratio, quick ratio, and cash ratio. Profitability aspects include gross profit margin, net profit margin, return of investment, and return on equity. Solvability aspects include debt to assets ratio, and debt to equity ratio.Result analysis and discussion show liquidity as measured by the current ratio, quick ratio and cash ratio shows the financial ability of PT. Indomarco Prismatama (Indomaret) is better than the financial ability of PT. Sigmantara Alfindo (Alfamart). financial performance from aspects of profitability as measured by gross profit margin ratio, net profit margin ratio, return on investment, return on equity indicates the ability of company PT. Indomarco Prismatama (Indomaret) in making better profits from PT. Sigmantara Alfindo (Alfamart), financial performance from the solvability aspects as measured by the debt to asset ratio and the dept to equity ratio shows that PT. Indomarco Prismatama (Indomaret) is always better than the ratio of PT. Sigamantara Alfindo (Alfamart), then the results of hypothesis analysis are accepted.